Problems of education, school system and upbringing as presented by Warsaw “Izraelita” in 1905-1915 - Agnieszka Wałęga (Studia z Teorii Wychowania)
The article presents the problems of education, school system and upbringing discussed in the Warsaw magazine “Izraelita”, an organ which supported the processes of assimilation of Jews, in the last 10 years of its existence, falling for the years 1905-1915. It was a time of dynamic political, social and cultural changes, which to a large extent also affected the scope and form of the Editorial Staff's approach to pedagogic issues. Apart from the general directions of the pedagogic interests of “Izraelita”, the article draws attention to several key issues for the analysed period, such as: growing manifestations of anti-Semitism in schools and the forms of responding to this phenomenon, discussion about the language of teaching, the beginnings of diverse discussions about the upbringing and education of women, and the necessity of taking into account the problems of upbringing and education of children with special needs.